Avaliação da silagem de grão úmido em substituição ao milho seco moído na terminação de novilhas - Gasparello, João Pedro (Universidade Federal de São Carlos, 2025)
The objective of the work was to analyze the finishing of 60 heifers aged around 18 months, with an average of 353 kg, with 30 heifers belonging to the control group, where a balanced diet was used with the use of finely ground corn, compared to another 30 heifers that were fed with moist corn grain silage (SGUM). Characteristics linked to animal performance were analyzed, such as daily weight gain, carcass yield, gain yield, average dry matter intake and diet cost and total feed cost. Regarding the results, there was no significant difference in relation to average daily weight gain (SGUM 0.946 and Control 1.017), carcass yield (both 0.5) and gain yield (both 0.53), however with regard to the cost of the diet and daily dry matter consumption (SGUM 8.52 and Control 9.58) a significant difference can be observed. In comparison between the types of corn processing, an improvement in feed efficiency of around 10% can be observed when using SGUM in the animals' diet.
Evaluation of moist corn grain silage as a replacement for ground corn in the finishing of heifers
Keywords: Bovinos; Nutrição; Eficiência alimentar; Cattle; Nutrition; Feed efficiency; CIENCIAS AGRARIAS::ZOOTECNIA::NUTRICAO E ALIMENTACAO ANIMAL; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL